Supernova neutrinos in a strangeon star model. (September 2017) - Yuan, Mao; Lu, Ji-Guang; Yang, Zhi-Liang; Lai, Xiao-Yu; Xu, Ren-Xin
Abstract: The neutrino burst detected during supernova SN 1987A is explained in a strangeon star model, in which it is proposed that a pulsar-like compact object is composed of strangeons ( strangeon : an abbreviation for "strange nucleon"). A nascent strangeon star's initial internal energy is calculated, with the inclusion of pion excitation (energy around 10 53 erg, comparable to the gravitational binding energy of a collapsed core). A liquid-solid phase transition at temperature ∼ 1−2 MeV may occur only a few tens of seconds after core collapse, and the thermal evolution of a strangeon star is then modeled. It is found that the neutrino burst observed from SN 1987A can be reproduced in such a cooling model.